2012
DOI: 10.1002/jsfa.5612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐pressure argon and nitrogen treatments on respiration, browning and antioxidant potential of minimally processed pineapples during shelf life

Abstract: Both HP Ar and HP N processing had beneficial effects on MP pineapples throughout 20 days of storage at 4 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…During 9 days at 4°C, there was a high reduction of ascorbic acid in the control samples (54%), a moderate reduction in U (38%) followed by UH (30%), and a low reduction in H (26%), thus demonstrating that high pressure treatments were effective in reducing the loss of ascorbic acid in fresh mushroom. This is in agreement with Wu et al (2012a) who reported that high pressure argon treatments were effective in reducing AA in pineapples.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…During 9 days at 4°C, there was a high reduction of ascorbic acid in the control samples (54%), a moderate reduction in U (38%) followed by UH (30%), and a low reduction in H (26%), thus demonstrating that high pressure treatments were effective in reducing the loss of ascorbic acid in fresh mushroom. This is in agreement with Wu et al (2012a) who reported that high pressure argon treatments were effective in reducing AA in pineapples.…”
Section: Resultssupporting
confidence: 93%
“…The mean of six readings at different locations was randomly taken on the cap and compared to an ideal mushroom. D E was described by the following equation (Wu et al, 2012a):…”
Section: Methodsmentioning
confidence: 99%
“…The mean of six readings at different locations was randomly taken on the cap and compared to an ideal mushroom. ΔE was described by the following equation (Wu et al 2012).…”
Section: Colourmentioning
confidence: 99%
“…Pharmaceutical, cosmetics and food industries are very interested in biologically active compounds found in several food by‐products, namely by‐products of fruits and vegetables. Pineapple ( Ananas comosus ) is the most processed tropical fruit, and world production of pineapple has been growing, as well as the production of processed pineapple, namely canned pineapple, and minimally processed pineapple . The industrial processing of pineapple, including minimal processing, generates a high quantity of by‐products, which generally represent more than 20% of the fruit.…”
Section: Introductionmentioning
confidence: 99%